The 5 K run in popular fiction: Reading about parkrun and couch to 5 K - Turner, Ellen (Frontiers in Sports and Active Living, 2023)
Recent years have witnessed great interest in mass-participation running events (Hindley, 2020), and organisations such as parkrun and fitness programmes like Couch to 5K, have been instrumental in enabling participation for inexperienced runners. Concomitant with this has been a number of fictional works which centre on the 5K run. I contend that exploring fictional texts can offer a fresh take on how movements such as parkrun and Couch to 5K have entered the popular imagination. The four texts explored are Wake’s Saturday Morning Park Run (2020), Park’s A Run in the Park (2019), Boleyn’s Coming Home to Cariad Cove (2022), and James’s I Follow You (2020). The analysis is arranged thematically around the categories of health promotion, individual transformation, and community building. I argue that these texts frequently operate as health promotional tools and can help familiarise would-be runners with how parkrun and Couch to 5K work.